Effects of exogenous spermidine on the morphology and physiology of two ecological grasses under flooding stress - Sun, Rui; Hu, Hui; Hu, Die; Yang, Yujie; Cheng, Zihan; Chen, Xiaohu; Fei, Yongjun (Frontiers in Plant Science, 2025)
This study used Elytrigia elongata and Cynodon dactylon × C. transvaalensis ‘Tifdwarf’ as experimental materials. Flooding stress was simulated by raising the water level 2 cm above the soil surface, while the control (CK) involved conventional water management. Three treatments were applied: flooding stress alone (FS), and flooding combined with 1 mmol/L spermidine (FP). Each treatment lasted for 5, 10 and 20 days. The aim was to investigate the impact of 1 mmol/L spermidine (Spd) on the growth and physiological responses of seedlings of both species subjected to different durations of flooding stress. The results showed that applying exogenous Spd under flooding conditions significantly increased the number of epidermal cells and biomass accumulation. Spd increased photosynthetic capacity by raising chlorophyll content and gas exchange parameters while reducing antioxidant enzyme activity. This elevated free-state Spd levels and enabled the removal of accumulated reactive oxygen species (ROS). Additionally, Spd promoted the accumulation of osmoregulatory substances, alleviating oxidative damage to membrane lipids and maintaining cellular osmotic potential. Consequently, Spd mitigated the adverse effects of flooding stress on plant growth. Correlation and principal component analyses of physiological and biochemical indicators confirmed that exogenous Spd improved flooding tolerance in both species. Notably, Elytrigia elongata exhibited greater tolerance to flooding, and the mitigating effects of Spd were more pronounced in this species under the same inundation conditions. Overall, this study provides a theoretical foundation for mitigating flooding induced damage in ecological grasses and offers insights into cultivating flooding tolerant grass species.